Unraveling the Density and Hardness of Sintered Hydroxyapatite: A Conclusive Comparison of Laboratory-Synthesized Versus Commercial Variants - Rizal Fauzuddin Noor Ramdhani; Bagas Haqi Arrosyid; Alfian Noviyanto (Chemistry Department, Faculty of Sciences and Mathematics, Diponegoro University, 2025)
Hydroxyapatite (HA) is a bioceramic widely utilized in the medical field as a substitute for bone and dental applications. The mechanical properties of HA are influenced by its microstructure, which varies based on the source of the material, whether it is commercially acquired or laboratory-synthesized. This study aims to investigate and compare the properties of commercially available HA with those of laboratory-synthesized HA, as well as their mixtures, focusing on density and hardness. To conduct this investigation, both laboratory-synthesized and commercial HA were sintered at temperatures of 800°C, 900°C, 1000°C, and 1100°C for a duration of two hours. Additionally, various mixtures of the two sources of HA were prepared in weight percent ratios of 0:100, 30:70, 50:50, 70:30, and 100:0 using a planetary ball mill, also for two hours. The density of sintered HA was determined using Archimedes’ principle, while its hardness was evaluated using a Vickers hardness tester. The findings revealed that laboratory-synthesized HA sintered at 1100°C exhibited the highest density and hardness, measuring 3.15 g/cm3 and 488.9 MPa, respectively. This superior performance can be attributed to the smaller particle size of the laboratory-synthesized HA, which enhances densification. The dense structure of the laboratory-synthesized HA results in reduced porosity and smaller grain sizes, as evidenced by scanning electron microscopy images. In contrast, the commercial HA achieved a density of only 3.00 g/cm3 at the same sintering temperature of 1100°C, attributable to poorer densification and a resultant porous microstructure. Notably, the mixture of commercial and laboratory-synthesized HA at a ratio of 30:70 demonstrated properties closely aligned with those of pure laboratory-synthesized HA, achieving a density of 3.14 g/cm3 and a hardness of 477.3 MPa. These results underscore the importance of source material and processing conditions in determining the mechanical properties of hydroxyapatite.